2012
DOI: 10.1177/1475090212445865
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural networks to the evaluation of the ultimate strength of uniaxially compressed welded stiffened aluminium plates

Abstract: A series of elastoplastic large-deflection finite element analyses is performed on stiffened aluminium plates with flat-bar stiffeners under in-plane longitudinal compression loads. Then, the closed-form ultimate compressive strength formula is derived for stiffened aluminium plates by regression analysis. Finally, artificial neural network methodology is applied to predict the ultimate strength of uniaxially compressed stiffened aluminium plates. It is found that artificial neural network models can produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Benson et al (2011) investigated the ultimate strength characteristics of aluminium plates for high-speed vessels. Artificial neural networks (ANNs) were applied by Zareei et al (2012) in order to evaluate the ultimate strength of uniaxially compressed welded stiffened aluminium plates. Also, the effects of geometrical imperfections on the ultimate strength of aluminium stiffened plates subject to combined longitudinal compression and lateral pressure were studied by Khedmati et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Benson et al (2011) investigated the ultimate strength characteristics of aluminium plates for high-speed vessels. Artificial neural networks (ANNs) were applied by Zareei et al (2012) in order to evaluate the ultimate strength of uniaxially compressed welded stiffened aluminium plates. Also, the effects of geometrical imperfections on the ultimate strength of aluminium stiffened plates subject to combined longitudinal compression and lateral pressure were studied by Khedmati et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to predict the ultimate strength of structural members using ANN. Zareei et al [6] estimated the ultimate strength of stiffened aluminum plates with flat-bar stiffeners under in-plane longitudinal compression loads using an ANN. When comparing this value with the ultimate strength obtained using empirical equations, it was confirmed that the model prediction was close to the FEM result.…”
Section: Introductionmentioning
confidence: 99%
“…Zareei et al [6] performed a series of elastoplastic large-deflection analyses of stiffened aluminum plates and applied artificial neural network to predict the ultimate compressive strength.…”
Section: Introductionmentioning
confidence: 99%